GRAPHIC TRAVELOGUE PADA DESTINATION BRANDING KAWASAN WISATA BALUWARTI - Muh. Zofwan Zarkasi; Asmoro Nurhadi Panindias (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Graphic Travelogue Baluwarti is the preferred strategy in favor of destination branding Baluwarti area. Wall which is a tourist area with a variety of building and environment cultural traditions that exist in it, must have a media campaign that one of them is unique Graphic Travelogue Baluwarti the form of books. Graphic Travelogue Baluwarti planned design is shaped like a travel diary of visitors (Consumers Journey) that contains images / photos and descriptions of attractions. Design sought to make public (visitors) feel the drive and diinfokan uniqueness Baluwarti area attractions.